Aplicación del modelo Black- Sholes-Merton en el estudio del comportamiento errático de los incrementos de caudales máximos (río Fonce, Santander) (2016)
This work is the result of the Scientific Research Project of New Granada Military University ING1544 of 2014, which was developed together with the University of Pamplona (Norte de Santander). This paper shows the application of the Black-Sholes-Merton (BSM) financial model transferred to the hydrological environment to study the erratic movements of the increases in peak flows of Fonce river (San Gil, Santander). For this purpose, the BSM stochastic differential equation is solved. Firstly, it was identified that the behavior of the maximum values of annual flows in the river Fonce is caused by a non-stationary process, since from the year 1980 their average increases. Afterwards, it was found that the behavior of the increases in the flow follows the properties of the Wiener process. Finally, a first approximation of the analytical solution BSM model is applied. The results show clearly a viability in modeling with stochastic differential equations of the flow behavior in the Fonce River.